2019
DOI: 10.1136/gpsych-2019-100153
|View full text |Cite
|
Sign up to set email alerts
|

Client-level predictors of treatment engagement, outcome and dropout: moving beyond demographics

Abstract: BackgroundDespite the availability of evidence-based treatments for posttraumatic stress disorder (PTSD), significant heterogeneity in the effectiveness of PTSD treatment persists, especially in community settings. Client demographics used to understand this variability in treatment outcome and dropout have yielded mixed results. Despite increasing evidence for the importance of attending to treatment engagement in community settings, few studies have explored client-level predictors.AimThe purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similarly, Larsen et al (2020) did not find that within treatment symptom increase predicted CPT dropout ( Larsen et al, 2020 ). In examining treatment process variables, Youn et al (2019) found that repeating treatment content during CPT to meet patient needs predicted treatment completion. While these quantitative studies examining potentially modifiable processes have furthered the literature on PE/CPT engagement, one-off findings without replication across studies continue to be the norm, and thus far, effective interventions for improving PE/CPT completion have remained elusive ( Kehle-Forbes & Kimerling, 2017 ).…”
mentioning
confidence: 99%
“…Similarly, Larsen et al (2020) did not find that within treatment symptom increase predicted CPT dropout ( Larsen et al, 2020 ). In examining treatment process variables, Youn et al (2019) found that repeating treatment content during CPT to meet patient needs predicted treatment completion. While these quantitative studies examining potentially modifiable processes have furthered the literature on PE/CPT engagement, one-off findings without replication across studies continue to be the norm, and thus far, effective interventions for improving PE/CPT completion have remained elusive ( Kehle-Forbes & Kimerling, 2017 ).…”
mentioning
confidence: 99%
“…Finally, caregivers in our Spanish intervention groups reported overall challenges and daily stresses less frequently than those in English groups. Qualitative accounts often suggest that EBIs are less acceptable and feasible with non-English delivery and that non-English-speaking participants are less engaged ( Barrera et al, 2017 ; Youn et al, 2019 ). This was not the case for Bridges, which was initially developed for Mexican-heritage families ( Gonzales et al, 2012 ), suggesting EBIs specifically designed for cultural groups are engaging for the target families.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to move beyond demographic characteristics and baseline symptom characteristics when examining predictors of PTSD treatment outcomes (Cooper et al, 2023; Rubel et al, 2017; Youn et al, 2019) and instead focus on identifying processes occurring during treatment that relate to outcomes. Such processes may be malleable and can serve as intervention targets to improve retention in care and symptom response.…”
Section: The Present Studymentioning
confidence: 99%